EVALUASI STATUS KESUBURAN TANAH ULTISOL PADA DUA PENGGUNAAN LAHAN DI DESA PAK BULU KECAMATAN ANJONGAN KABUPATEN MEMPAWAH - Wati, Khairun Rahmah; Hazriani, Rini; Manurung, Rinto (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Ultisols generally have low soil fertility status due to their acidic nature, low organic matter, and limited nutrient availability. The utilization of ultisols for oil palm plantations and secondary forests certainly affects the availability of nutrients, organic matter, and soil acidity. Soil management that does not align with the fertility conditions will result in other problems that can threaten the sustainability of agricultural production. The lack of comprehensive research on soil fertility, particularly in Pak Bulu Village, Anjongan Sub-District, limits the available information on the long-term impacts that could affect soil quality. This situation highlights the importance of conducting this research to determine the appropriate land management practices for soil fertility in each land use. This study employed a soil survey method, with sampling points determined by overlaying maps of soil types, slope classes, and land use, using a purposive sampling method, which was divided into four land units. The soil samples were analyzed for their chemical properties in the Soil Chemistry and Fertility Laboratory of the Faculty of Agriculture, Tanjungpura University. The laboratory results were then categorized based on the criteria for evaluating soil chemical properties by the Soil Research Center (1983), and the soil fertility status was subsequently evaluated based on the soil fertility evaluation guidelines by the Soil Research Center Bogor (1995). The evaluation results showed that the soil fertility status of both land uses was at the same level; however, the oil palm plantation had limiting factors such as Cation Exchange Capacity (CEC), Base Saturation (BS), Total Phosphorus (P-total), and Total Potassium (K-total) that were classified as low to very low, while the secondary forest only had Base Saturation and Total Potassium classified as very low, with CEC classified as low.